Os labirintos da memória em Orfãos do Eldorado de Milton Hatoum - Lemos, Vivian de Assis [UNESP]; Martha-Toneto, Diana Junkes Bueno [UNESP] (My University, 2012)
This article aims to analyze aspects of Orfãos do Eldorado (2008), by Milton Hatoum, to elucidate the plot construction by the use of memory, which articulates three narrative perspectives: the mythic, the social-historic and the mythic-social-personal. This process presents as a result a textual configuration marked by a contemporary diction, by the creative work and by a certain lyricism that allows us to say, as Tania Pellegrini and Alfredo Bosi, that there is a ‘revisitated’ regionalism in this author work.

Este artigo busca analisar aspectos da obra Órfãos do Eldorado (2008), de Milton Hatoum, com o intuito de elucidar a construção do enredo por meio da utilização da memória que articula três planos possíveis de narrativa: a mítica, a histórico-social e a mítico-histórico pessoal. Esse processo tem como resultado a configuração de um texto marcado por dicção contemporânea, pelo rigor criativo e por certo lirismo, responsáveis pelo desenho do regionalismo revisitado que Tania Pellegrini e Alfredo Bosi atribuem ao fazer narrativo de Hatoum.
Keywords: Milton Hatoum; Órfãos do Eldorado; literatura brasileira contemporânea; narrativa poética; memória e trauma; lenda do Eldorado; memory; history; myth; Eldorado tale